Ant Fauna Diversity in an Area Degraded by Diamond Mining in the State of Mato Grosso,Brazil - Rocha, Wilian de Oliveira (2014)
This study aimed at sampling the diversity of ants in environments influenced by diamond mining activities in the Brazilian savannah, providing information on the ant fauna in this region of Mato Grosso.The study was carried out in the city of Poxoréu-MT, Brazil, in a property with diamond mining,where pitfall traps were installed in four different transects per environment: A1 – degraded area by diamond mining A2 – adjacent area to A1 with savannah vegetation with anthropogenic influence, A3 – adjacent area to A2 with anthropized savannah vegetation, bordering with A4 – area with savannah vegetation preserved without anthropogenic changes. Samples were collected bimonthly for a period of one year, and the samples were quantified and identified taking into account their species level in order to allow the application of the diversity indices for each environment. 15 species of ants were sampled among the four environments, being nine species in A1, 13 in A2, 15 in A3 and 12 species in A4, presenting Brachymyrmex patagonicus as the most abundant, foraging in all environments. Diversity indices allow to conclude that A3 has the greatest diversity of species, and conversely the lower dominance, in all environments. However, A1 was the most dominant species of ants due to the lowest diversity. Thus, environmental degradation by diamond mining can affect the composition of ants and their dominance in the savannah vegetation.